Humans Share More Preferences for Floral Phenotypes With Pollinators Than With Pests - Ruiz-Hernández, Victoria; Joubert, Lize; Rodríguez-Gómez, Amador; Artuso, Silvia; Pattrick, Jonathan G.; Gómez, Perla A.; Eckerstorfer, Sarah; Brandauer, Sarah Sophie; Trcka-Rojas, Carolina G. I.; Martínez-Reina, Luis; Booth, Josh; Lau-Zhu, Alex; et al. (Frontiers in Plant Science, 2021)
Studies on the selection of floral traits usually consider pollinators and sometimes herbivores. However, humans also exert selection on floral traits of ornamental plants. We compared the preferences of bumblebees (Bombus terrestris), thrips (Frankliniella occidentalis) and humans for flowers of snapdragon. From a cross of two species, Antirrhinum majus and A. linkianum, we selected 4 Recombinant Inbred Lines (RILs). We characterized scent emission from whole flowers and stamens, pollen content and viability, total sugar in nectar, trichome density, floral shape, size and colour of floral parts. We tested the preferences of bumblebees, thrips and humans for whole flowers, floral scent bouquets, stamen scent and individual scent compounds. Humans and bumblebees showed preferences for parental species whereas thrips preferred RILs. Colour and floral scent, in combination with other floral traits, seem relevant phenotypes for all organisms. Remarkably, visual traits override scent cues for bumblebees, although scent is an important trait when bumblebees cannot see the flowers and methyl benzoate was identified as a key attractant for them. The evolutionary trajectory of flowers is the result of multiple floral traits interacting with different organisms with different habits and modes of interaction.